Sequence-dependent structural variations of DNA revealed by DNase I. - Brukner, I (1990)
Two global helix parameters important for DNA-DNase I interaction are the geometry of the minor groove and the DNA stiffness that resists bending toward major groove. Thus, local averaging of P-O3' bonds cutting frequencies (InP) reflects global helix parameters revealed by DNase I. Using the approximation that locally averaged InP values depend only on the type of the dinucleotide steps involved in the region of interaction, we calculated the collective contribution (sigma Dd) for ten different dinucleotide steps. Our results suggest that, at the first approximation, global varying helix parameters revealed by DNase I, might be predicted from sequence. Obtained sigma Dd function can be used as a sequence-dependent measure of protein-induced DNA flexure in the direction towards the major groove, which is usually connected to widening of the minor groove. In the course of analysis of Mg2+ and Mn2+ dependent DNase I digestions, no significant difference was found, in spite of the supposed differences in enzyme activity. These results suggest that if the second Mn2(+)-dependent active site exists, its activity is lower than that of the first one.